Obstetric, Neonatal, and Clinical Outcomes of Day 6 vs. Day 5 Vitrified-Warmed Blastocyst Transfers: Retrospective Cohort Study With Propensity Score Matching - Park, Dong Soo; Kim, Ji Won; Chang, Eun Mi; Lee, Woo Sik; Yoon, Tae Ki; Lyu, Sang Woo (Frontiers in Endocrinology, 2020)
Despite the large number of studies on blastocyst transfers, it is unclear whether day 6 blastocysts have similar pregnancy rates and safety with day 5 blastocysts. Thus, this study aimed to compare the obstetric, neonatal, and clinical outcomes of day 5 and day 6 vitrified blastocyst transfers (VBT). In this retrospective cohort study with propensity score matching, we evaluated 1313 cycles of VBT performed between January 2014 and December 2015 at the Fertility Center of CHA Gangnam Medical Center. All cycles underwent natural endometrial preparation. We used propensity score matching to compare day 5 and day 6 VBTs in a matched comparison. After propensity score matching, there were 465 cycles of day 5 VBT and 155 cycles of day 6 VBT. Implantation rate (IR), clinical pregnancy rate (CPR), and live birth rate (LBR) were significantly lower in day 6 VBTs (44.2% vs. 53.1%, p=0.023; 48.4% vs. 60.4%, p=0.009; 33.5% vs. 51.8%, p <0.001). Miscarriage rate was significantly higher in day 6 VBTs (29.3% vs. 10.7%, p <0.001). Rate of multiple gestations was similar between the two groups (29.3% vs. 30.2%, p =0.816). Assessing 241 and 52 babies from day 5 and day 6 VBTs, no differences were found in neonatal outcomes including rates of low birth weight, preterm birth, and congenital malformations. In propensity score-matched analysis, obstetric and neonatal outcomes between day 5 and day 6 VBTs were similar so that day 6 VBTs are as safe as day 5 VBTs. IR, CPR, and LBR were are all significantly lower in day 6 VBTs. Therefore, if there are no differences in the morphological grade between day 5 and day 6 blastocysts, transfer of day 5 vitrified blastocyst should be considered first.